The Impact of Various Culture Conditions on Human Mesenchymal Stromal Cells Metabolism. (1st March 2021) - Tonarova, Pavla; Lochovska, Katerina; Pytlik, Robert; Hubalek Kalbacova, Marie
Abstract : In vitro and in vivo analyses are closely connected, and the reciprocal relationship between the two comprises a key assumption with concern to the conducting of meaningful research. The primary purpose of in vitro analysis is to provide a solid background for in vivo and clinical study purposes. The fields of cell therapy, tissue engineering, and regenerative medicine depend upon the high quality and appropriate degree of the expansion of mesenchymal stromal cells (MSCs) under low-risk and well-defined conditions. Hence, it is necessary to determine suitable alternatives to fetal bovine serum (FBS—the laboratory gold standard) that comply with all the relevant clinical requirements and that provide the appropriate quantity of high-quality cells while preserving the required properties. Human serum (autologous and allogeneic) and blood platelet lysates and releasates are currently considered to offer promising and relatively well-accessible MSC cultivation alternatives. Our study compared the effect of heat-inactivated FBS on MSC metabolism as compared to its native form (both are used as the standard in laboratory practice) and to potential alternatives with concern to clinical application—human serum (allogeneic and autologous) or platelet releasate (PR-SRGF). The influence of the origin of the serum (fetal versus adult) was also determined. The results revealed the key impact of the heat inactivation of FBS on MSCs and the effectiveness of human sera and platelet releasates with respect to MSC behaviour (metabolic activity, proliferation, morphology, and cytokine production).